HUBUNGAN KOMUNIKASI, POLA ASUH, DAN PEKERJAAN ORANG TUA TERHADAP KEJADIAN TEMPER TANTRUM ANAK USIA 36-60 BULAN DI PUSKESMAS LEREP - Muhammad Firdaus Riza Arli Putra; Agus Saptanto; Andra Novitasari; Oky Rahma Prihandani (CV. Adiba Aisha Amira, 2025)
The Relationship Between Communication, Parenting Styles, and Parents' Employment on Temper Tantrums in Children Aged 36-60 Months at the Lerep Community Health Center. Momentary outbursts of extreme, unpleasant, and often violent conduct brought on by annoyance or fury are known as temper tantrums. Temper tantrums in Indonesia within one year, 23-83% have experienced temper tantrums aged 2-4 years. The goal of this research is to establish whether parents' occupations, parenting styles, and communication styles have any bearing on their children's rates of temper outbursts between the ages of 36 and 60 months. This study was an analytical observational study using a cross-sectional methodology and the technique of successive sampling. The mother were employed as the study sample. Data analysis on this communication, parenting patterns, and parents occupational towards temper tantrums of children aged 36-60 months using contingency coefficient statistic test. The study instrument used a temper tantrum questionnaire, a parenting style questionnaire, and a communication questionnaire. A total of 64 respondents who became the research sample. A connection between communication and temper tantrums to the tune of a 0.607 correlation coefficient. A link of 0.624 was found between parental style and outbursts of anger in children. A connection between parents' occupatonal and temper tantrums to the tune of a 0.265. The variable that most influences frequency of temper outbursts in 36-to-60-month-old children at the Lerep Puskesmas is communication with a p value of 0.000. A connection exists between communication and parenting patterns toward temper tantrums in 36-60 month-old children at the Lerep Puskesmas. Parental profession has no bearing on the frequency or severity of children's tantrums aged 36-60 months at the Lerep Puskesmas. The variable that most influences a child's temper tantrums are parenting patterns.